Analysis of the Impact of Technological Change on Marketing Practices - Setiawan, Zunan; Sinaga, Hommy Dorthy Ellyany; A., Chevy Herli Sumerli; Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2023)
This research investigates the impact of technological change on the marketing practices of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a comprehensive quantitative analysis. Surveys were conducted among a diverse sample of 500 MSMEs, spanning various sectors. The findings reveal a landscape of varied technological adoption, with financial constraints and a digital skills gap emerging as predominant challenges. Nevertheless, the study highlights the transformative potential of technology, showcasing improved customer engagement, expanded market reach, and enhanced performance metrics. The synthesis of results informs practical strategies for MSMEs, policy recommendations for stakeholders, and avenues for future research. This research contributes valuable insights into the nuanced relationship between technology and MSMEs, offering a foundation for informed decision-making in the rapidly evolving digital landscape.